The Effect of Traffic Jam on High Levels of Student Stress - Amelia, Alfara Dhita; Arib, Muhammad Irfan; Renaldi, Yohanes Soreth; Hartono, Tania Sunilah; Ramos, Sarah Vega (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2023)
Traffic Jam is a problem that is quite complicated in the community. The volume of transportation passing by on the highway is a trigger for traffic jam. This unresolved traffic jam is causing stress to road users. So that, this study aims to see how far the impact of traffic jams has on student life and the level of student stress in dealing with traffic jams. This study uses a quantitative research method with an explanatory approach. The population in this study were 293 students of the Communication Studies Program, Mercu Buana University Yogyakarta batch 2021, while the sample was taken using probability sampling technique, namely Simple Random Sampling so that a sample of 101 students was obtained. The data collection technique used was a questionnaire on the influence of media use and a questionnaire on fulfilling information needs. The data obtained was analyzed using SPSS Version 20 software. The results showed that there was a strong relationship between student stress levels and traffic jams in the city of Yogyakarta. Furthermore, there is an influence of 53.2% between the effect of traffic jams on the high level of student stress. So that the other 46.8% is influenced by other variables not examined. Furthermore, the results of the independent sample t-test showed no difference in the effect of traffic jams between male and female students.